Bispecific T-cell engager (BiTE) antibody construct blinatumomab for the treatment of patients with relapsed/refractory non-hodgkin lymphoma: final results from a phase I study - Goebeler, Maria-Elisabeth; Nagorsen, Dirk (Journal of clinical oncology, 2016)
PurposeBlinatumomab is a CD19/CD3 BiTE (bispecific T-cell engager) antibody construct for the treatment of Philadelphia chromosome-negative acute B-lymphoblastic leukemia. We evaluated blinatumomab in relapsed/refractory B-cell non-Hodgkin lymphoma (NHL).Patients and MethodsThis 3 + 3 design, phase I dose-escalation study determined adverse events and the maximum tolerated dose (MTD) of continuous intravenous infusion blinatumomab in patients with relapsed/refractory NHL. Blinatumomab was administered over 4 or 8 weeks at seven different dose levels (0.5 to 90 μg/m2/day). End points were incidence of adverse events, pharmacokinetics, pharmacodynamics, and overall response rate.ResultsBetween 2004 and 2011, 76 heavily pretreated patients with relapsed/refractory NHL, who included 14 with diffuse large B-cell lymphoma, were enrolled; 42 received treatment in the formal dose-escalation phase. Neurologic events were dose limiting, and 60 μg/m2/day was established as the MTD. Thirty-four additional patients were recruited to evaluate antilymphoma activity and strategies for mitigating neurologic events at a prespecified MTD. Stepwise dosing (5 to 60 μg/m2/day) plus pentosan polysulfate SP54 (n = 3) resulted in no treatment discontinuations; single-step (n = 5) and double-step (n = 24) dosing entailed two and seven treatment discontinuations due to neurologic events, respectively. Grade 3 neurologic events occurred in 22% of patients (no grade 4/5). Among patients treated at 60 μg/m2/day (target dose; n = 35), the overall response rate was 69% across NHL subtypes and 55% for diffuse large B-cell lymphoma (n = 11); median response duration was 404 days (95% CI, 207 to 1,129 days).ConclusionIn this phase I study of relapsed/refractory NHL, continuous infusion with CD19-targeted immunotherapy blinatumomab at various doses and schedules was feasible, with an MTD of 60 μg/m2/day. Single-agent blinatumomab showed antilymphoma activity.